Exploring Metaphors in the Embroidery of the Punjab: A Study of the Inscriptions at Bahāuddīn Zakariyā Shrine (Al-Qamar, 2021)
This study is all about the investigation of symbolic representation of inscriptions at Bahāuddīn Zakariyā & Shah Rukn-i-Ālam, their relation to religion and culture as Multan was the main route where business took place. Additionally, Sufi culture & faith of regional occupants also had an effect on these symbols. Multan remains acclaimed for its shrines; mainly, Bahāuddīn Zakariyā & Shah Rukn-i-Ālam which is taken as an inspiration to discover a connection between visual (design) and literary (inscriptions) references translated in thread crafts of Multan. Inscriptions and calligraphy contain symbolism connecting from Qur’ānic verses to plants, seeds, birds and animals. Crafts visual vocabulary is constructed with it.
Keywords: Multan; shrines; symbols; inscriptions; thread crafts